Building a better Psylloidea (Hemiptera) trap? A field-look at a prototype trap constructed using three-dimensional printer technology. Issue 1 (10th December 2018) - Horton, David R.; Miliczky, Eugene R.; Lewis, Tamera M.; Wohleb, Carrie H.; Waters, Timothy D.; Dickens, Anthony A.; Halbert, Susan E.; Ramadugu, Chandrika; Jensen, Andrew S.
Abstract: An insect trap constructed using three-dimensional (3D) printing technology was tested in potato ( Solanum tuberosum Linnaeus; Solanaceae) fields to determine whether it could substitute for the standard yellow sticky card used to monitor Bactericera cockerelli (Šulc) (Hemiptera: Psylloidea: Triozidae). Sticky cards have shortcomings that prompted search for a replacement: cards are messy, require weekly replacement, are expensive to purchase, and accumulate large numbers of nontarget insects. Bactericera cockerelli on sticky cards also deteriorate enough that specimens cannot be tested reliably for the presence of vectored plant pathogens. A prototype trap constructed using 3D printing technology for monitoring Diaphorina citri Kuwayama (Hemiptera: Psylloidea: Liviidae) was tested for monitoring B. cockerelli . The trap was designed to attract B. cockerelli visually to the trap and then funnel specimens into preservative-filled vials at the trap bottom. Prototype traps were paired against yellow sticky cards at multiple fields to compare the captures of B. cockerelli between cards and traps. The prototype trap was competitive with sticky cards early in the growing season when B. cockerelli numbers were low. We estimated that two or three prototype traps would collect as many B. cockerelli as one sticky card under these conditions. Efficacy of the prototype declined as B. cockerelli numbers increased seasonally. The prototype trap accumulated nontarget taxa that are common on sticky cards (especially Thysanoptera and Diptera), and was also found to capture taxa of possible interest in integrated pest management research, including predatory insects, parasitic Hymenoptera, and winged Aphididae (Hemiptera), suggesting that the traps could be useful outside of the purpose targeted here. We believe that 3D printing technology has substantial promise for developing monitoring tools that exploit behavioural traits of the targeted insect. Ongoing work includes the use of this technology to modify the prototype, with a focus on making it more effective at capturing psyllids and less susceptible to capture of nontarget species.